Customary Law as an Ecological Mechanism: A Literature Review of the Socio-Ecological System of the Kajang Tribe in South Sulawesi - Suwandi; Putri, Riska; Ardhiansyah, Septian Syahnam; Aribowo, Pinkan Claudia; Rosyid, Nurfaizal (CV. Kurnia Grup, 2025)
Customary law is a collective value system that originates from local wisdom and is passed down from generation to generation within indigenous communities. This study aims to examine the role of Ammatoa customary law in the Kajang tribe community in South Sulawesi as an ecological mechanism based on spirituality and social structure. Using a descriptive qualitative approach with a literature review method, this study examines relevant scientific literature on the structure of customary law, the values of Pasang ri Kajang, the principle of kamase-mase, and the Patuntung belief system. The results of the study show that Kajang customary law not only regulates social relations but also protects the environment through customary prohibitions, the division of sacred zones, a social sanction system based on siri’, and collective governance led by Ammatoa. This system reflects living law and operates effectively without state intervention. Customary law has proven to be more adaptive and adhered to because it is based on moral and spiritual legitimacy, not formal legal coercion. Additionally, these findings indicate that synergy between customary law and state law is feasible to strengthen national conservation policies that are ecologically just. Therefore, customary law must be substantively recognized as a partner in sustainable environmental governance in Indonesia.